Foraminiferal Patterns of the Arctic Ocean. - Clark,David L.; Larson,John A.; Root,Ruth E.; Fagerlin,Stan C. (1975)
The details of planktonic and benthonic Foraminifera distribution in nine representative cores has been selected as a method to illustrate Arctic Ocean Late Cenozoic faunal patterns. The cores selected represent some of the most complete and unambiguous cores in terms of magnetic stratigraphy and fauna. The results are representative of actual patterns seen in many other cores. Taken together, the data on planktonic and benthonic Foraminifera give some idea of the Foraminiferal assemblages during much of the Pliocene and Pleistocene in the Arctic Ocean. The cores have been obtained from operations on ice-island T-3, since 1963.